1952
DOI: 10.1021/j150501a018
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Fluorides of Metals in Liquid Hydrogen Fluoride

Abstract: up to the moment of reaction. The large reaction distance and small electrostatic contribution in system 3 may thus find an explanation. Of the halogens it appears that only the F~ion has any substantial solvation28 but data for F~substitution are not available to check this interesting correlation between electrolytic and kinetic behavior of ions.The thiosulfate ion is strictly not spherically symmetrical but the double charge may be regarded as "smearing out" any such deviations. This double charge increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1963
1963
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Magnesium was investigated as a possible working electrode because of the low solubility of the fluoride in HF. The solubility of MgF 2 at -3,3°C is 0.025 g/lO0 g HF (2). Preliminary experiments with magnesium have included weight loss measurements and polarization curves in anhydrous HF.…”
Section: A Magnesiummentioning
confidence: 99%
“…Magnesium was investigated as a possible working electrode because of the low solubility of the fluoride in HF. The solubility of MgF 2 at -3,3°C is 0.025 g/lO0 g HF (2). Preliminary experiments with magnesium have included weight loss measurements and polarization curves in anhydrous HF.…”
Section: A Magnesiummentioning
confidence: 99%
“…Thus it is known Russian Chemical Reviews, 39 (12), 1970 that these compounds undergo self-ionisation in the liquid state 12 " 15 : and numerous studies in recent years have shown that their interaction with many inorganic fluorides is due to the presence of the above ions in solution and the formation of the fluorohalogenates MXF n+1 (MF.XF n ) can itself be regarded as the solvation of fluorides by the halogen fluoride 16 » 17 . The solvating capacity of hydrogen fluoride is well illustrated by the data of Jache and Cady 18 , who established that highly soluble fluorides exhibit a greater capacity for combining with hydrogen fluoride. However, they quote only the approximate composition of the solid phase in the saturated solutions of fluorides in hydrogen fluoride after centrifugation and therefore their results cannot be regarded as final proof of the existence of definite solvates as individual compounds.…”
mentioning
confidence: 90%
“…The possibility of synthesising alkaline earth metal hydrogen fluorides from aqueous hydrofluoric acid solutions was previously considered unlikely 8 , although the data of Jache and Cady 18 indicated a tendency by these fluorides to combine with HF. In a study of the HF- Recent studies on the HF-MF 2 -H 2 O (M = Cu, Zn, Cd) systems 75 , 76 showed that, despite their very low solubility in anhydrous hydrogen fluoride and its concentrated solutions, the fluorides of copper, zinc, and cadmium also form the hydrogen fluorides CuF 2 .3HF, ZnF 2 .2HF, and CdF 2 .HF.…”
Section: Synthesis Of Metal Hydrogen Fluoridesmentioning
confidence: 99%
“…For this purpose, the following metals have been obtained in the form of 1/8" diameter rods suitable for electrodes: antimony, 99.999%; bismuth, 99.999%; cobalt, 99.6%; copper, 99.9?%; iron, 99.9%; magnesium, 99.95%; silver, 99.9%; thallium, 99.999%; and titanium, 99.9%. These metals were selected both on the basis of previous experience (refs 8 and 9) and from a consideration of the solubilities of their fluorides (ref 10). It is hoped that one of those metals which have two oxidation states, with the fluoride of the higher oxidation state more insoluble than the lower, will possibly exhibit the type of passivity desired.…”
Section: Future Course Of the Workmentioning
confidence: 99%